2015
DOI: 10.4103/2249-4863.174264
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine education in India: A panoramic view

Abstract: Introduction:In the recent years, there has been renewed interest in strengthening primary care for improved health services delivery. Family medicine with its holistic principles is an effective approach for building primary care workforce in resource constraint settings. Even though this discipline is well established and mainstreamed in Western countries, the same is yet to occur in low- and middle-income nations. India with its paradigm shift for universal health coverage is strategically poised to embrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Hopayian et al (2018) have recently found that the PBL technique to train Armenian FMRs could significantly improve levels of active learning and FMR-patient contact with an escalation in motivation and engagement of FMRs during their training times. Pati et al (2015) mentioned that the curriculum of FM in India primarily is problem-based which was consistent with the findings of the present study. Such training would increase the number of competent physicians in meeting the health needs of the community.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hopayian et al (2018) have recently found that the PBL technique to train Armenian FMRs could significantly improve levels of active learning and FMR-patient contact with an escalation in motivation and engagement of FMRs during their training times. Pati et al (2015) mentioned that the curriculum of FM in India primarily is problem-based which was consistent with the findings of the present study. Such training would increase the number of competent physicians in meeting the health needs of the community.…”
Section: Discussionsupporting
confidence: 91%
“…Singapore, Malaysia, Philippines, Nepal and Pakistan have residency programs managed by university departments of family medicine in partnership with the health department (Pati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This leaves nearly half the student population in the dark about a specialty that has an important role to play in addressing crucial health care issues of equity, continuity of care, cost effectiveness, and holistic care that is patient centric. [ 4 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…diplomas, postgraduate, doctoral). To go beyond community and individual care and observe a macro-level lens of training, this research study focused on programs where training involved broader aspects of public health and not specialized community medicine programs with a more clinical focus (10,11), and thus we excluded the latter from the desk review.…”
Section: Desk Reviewmentioning
confidence: 99%